2017
DOI: 10.1021/acs.accounts.7b00055
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Complexes of Metal Oxide Clusters for Versatile Self-Assemblies

Abstract: The combination of rational design of building components and suitable utilization of driving force affords spontaneous molecular assemblies with well-defined nanostructure and morphology over multiple length scales. The serious challenges in constructing assemblies with structural advantages for the realization of functions programmed into the building components usually lie ahead since the process that occurs does not always follow the expected roadmap in the absence of external intervention. Thus, prefabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
111
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 61 publications
2
111
0
3
Order By: Relevance
“…As shown in Figure a, upon the addition of cation amphiphile C 12 mimBr into EuW 10 aqueous solution, a clear enthalpy change was observed and the binding constant was 3.31×10 3 m −1 , indicating that significant electrostatic interaction was present between the [EuW 10 O 36 ] 9− anion and [C 12 mim] + cation. Similar to other cationic amphiphile‐POM self‐assemblies, the obtained complex is water‐insoluble . However, for the EuW 10 /C 12 IPS aqueous system, no significant enthalpy change was observed (Figure b) and a clarified aqueous solution was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a, upon the addition of cation amphiphile C 12 mimBr into EuW 10 aqueous solution, a clear enthalpy change was observed and the binding constant was 3.31×10 3 m −1 , indicating that significant electrostatic interaction was present between the [EuW 10 O 36 ] 9− anion and [C 12 mim] + cation. Similar to other cationic amphiphile‐POM self‐assemblies, the obtained complex is water‐insoluble . However, for the EuW 10 /C 12 IPS aqueous system, no significant enthalpy change was observed (Figure b) and a clarified aqueous solution was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…POM cores can be abstracted as an ideal ball model with six equal faces.The packing geometry can be ascribed to the occupation of the zwitterionic amphiphiles on the POM core.D ifferent from the organic solvent environment, alkyl chains tend to aggregate on one side of the POM core instead of symmetric distribution in aqueous solution. [14] For the case of molar ratio greater than 4:1( surface occupation > 2/3), we propose that the aggregation morphology depends mainly upon the molecular configuration of C 16 IPS,while the main effect of POM is to increase the solubility of C 16 IPS and screen the electrostatic repulsions among zwitterions. [14] When 1/3 < surface occupation 2/3 (3:1 and 4:1), cone-shaped geometry occurs owing to the increase of hydrocarbon chain volume,a nd columnar packing becomes the favorable packing state.…”
mentioning
confidence: 84%
“…[10] Spontaneous self-assembly of weakelectrolyte type POMs into vesicle-like supramolecular structures has been confirmed by Liu et al [11] Nevertheless, the assistance from grafting groups or counterions has been demonstrated to be more effective in constructing POM selfassemblies. [14] However, the cationicamphiphile-POM ionic complexes could only disperse in organic media because of the strong electrostatic adsorption of hydrophobic cations. [14] However, the cationicamphiphile-POM ionic complexes could only disperse in organic media because of the strong electrostatic adsorption of hydrophobic cations.…”
mentioning
confidence: 99%
See 2 more Smart Citations